Neonatal and Pediatric Emergency Room Visits in a Tertiary Center during the COVID-19 Pandemic in Italy - Davide Silvagni; Laura Baggio; Patrizia Lo Tartaro Meragliotta; Pietro Soloni; Giovanna La Fauci; Chiara Bovo; Stefania Ielo; Paolo Biban (Pediatric Reports, 2021)
The COVID-19 pandemic is affecting healthcare services worldwide. We investigated the impact of a strict lockdown policy on the characteristics of neonatal and pediatric attendances to our pediatric emergency department (PED). The clinical features of PED visits in March–April 2020 (COVID-19) and March–April 2019 (non-COVID-19) were analyzed. During the COVID-19 lockdown period, visits reduced by 67%, from 3159 to 1039. Neonatal access decreased from 78 to 59, mainly due to fewer pathological conditions, with a complete disappearance of respiratory infections. On the other hand, minor neonatal clinical conditions rose from 44 (56.4%) to 48 (81.4%), mostly due to feeding-related issues. Communicable diseases, particularly respiratory infections and gastroenteritis, dropped from 1552 (49.1%) to 288 (27.7%). Accident-related visits also decreased during COVID-19, from 535 (16.9%) to 309 (29.7%), becoming the most common cause of PED access. Hospital admissions reduced from 266 to 109, while PICU (pediatric intensive care unit) admissions decreased from 27 to 11, with a comparable rate of 10.1% in both periods. The lockdown due to COVID-19 had a substantial impact on our PED visits, which markedly decreased, mainly due to fewer respiratory infections. Unexpectedly, neonatal visits for minor conditions did not decline, but rather slightly increased. Among the children admitted to the PICU, none had respiratory disease.